2009
DOI: 10.1086/590263
|View full text |Cite
|
Sign up to set email alerts
|

Living at Extremes: Development at the Edges of Viable Temperature under Constant and Fluctuating Conditions

Abstract: In the painted turtle (Chrysemys picta) and the red-eared slider (Trachemys scripta), the temperature that eggs are exposed to during incubation influences many traits of the developing embryo. We tested the effect of fluctuating- versus constant-temperature incubation regimes at the high and low ends of the viable developmental temperature range to assess the effect of incubation environment on offspring development. Eggs were incubated in four treatments: 23 degrees C constant, 23 degrees +/- 3 degrees C, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 34 publications
6
79
0
Order By: Relevance
“…Reduced immunocompetence in young individuals has been shown in a few bird species (reviewed by Hausmann et al, 2005), and is thought to be due to a costly and protracted development of the immune system. Recent research on painted turtles has revealed that hatchling immune function depends on incubation temperatures (Les et al, 2009), thus, variation among the measures of immune function employed in the current study may reflect effects of the nest environment on development of the immune system.…”
Section: Discussion Age Effects: Development and Senescencementioning
confidence: 96%
See 1 more Smart Citation
“…Reduced immunocompetence in young individuals has been shown in a few bird species (reviewed by Hausmann et al, 2005), and is thought to be due to a costly and protracted development of the immune system. Recent research on painted turtles has revealed that hatchling immune function depends on incubation temperatures (Les et al, 2009), thus, variation among the measures of immune function employed in the current study may reflect effects of the nest environment on development of the immune system.…”
Section: Discussion Age Effects: Development and Senescencementioning
confidence: 96%
“…Physiological maintenance in a long-lived ectotherm Physiological maintenance has been widely studied in birds, mammals and invertebrate model systems, but much less is known about maintenance in ectothermic vertebrates [e.g. reptiles (Saad and El Ridi, 1988;Patnaik, 1994;Nelson and Demas, 1996;Zapata et al, 1992;Muñoz and de la Fuente, 2004;Madsen et al, 2007;Martin et al, 2008;Pitol et al, 2008;Les et al, 2009;Paitz et al, 2009;Sparkman and Palacios, 2009;Zimmerman et al, 2010)]. Ectothermic vertebrates have traits that suggest physiological maintenance patterns should deviate from those seen in previously studied endothermic vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the more obvious terrestrial ectotherms in an ecosystem are the reptiles, for which the thermal biology is especially well studied, making them ideal model organisms for this research. For example, incubation temperatures in reptiles can affect hatching success and hatchling phenotype (Hare et al, 2002;Shine et al, 1997), as well as subsequent growth (Nelson et al, 2004), survival (Hare et al, 2004), immune response (Les et al, 2009) and reproductive success (Warner et al, 2010). Thus, there are both direct and latent thermal effects associated with the incubation environment of reptiles.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating hatching success have shown that there is a range of temperatures in which embryos develop successfully, with hatching success dramatically declining at extremes of the temperature range. The same studies have found that within the range of temperatures that produce viable hatchlings, development tends to proceed more rapidly at higher temperatures (Booth, 1998;Les et al, 2009;). These data, while valuable, do not necessarily reflect the developmental and phenotypic responses to temperature variation inherent to in situ incubation environments.…”
mentioning
confidence: 87%